Змееныш: [фантастический роман] / Андрей Левицкий, Лев Жаков - Левицкий Андрей Юрьевич (S.T.A.L.K.E.R., 2010)
Экземпляры: аб. (20180412) / Инвентарный номер: 58240 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Л 37 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445